2022
DOI: 10.3390/microorganisms10020326
|View full text |Cite
|
Sign up to set email alerts
|

Stool Microbiota Diversity Analysis of Blastocystis-Positive and Blastocystis-Negative Individuals

Abstract: Blastocystis is a unicellular eukaryote found in the gastrointestinal tract of both human and other animal hosts. The clinical significance of colonic Blastocystis colonization remains obscure. In this study, we used metabarcoding and bioinformatics analyses to identify differences in stool microbiota diversity between Blastocystis-positive and Blastocystis-negative individuals (n = 1285). Alpha diversity was significantly higher in Blastocystis carriers. At phylum level, Firmicutes and Bacteroidetes were enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 16 publications
(26 reference statements)
0
25
1
Order By: Relevance
“…A reduction in intestinal microbiota diversity has been observed in a series of digestive diseases, such as IBD and IBS, that are associated with inflammation of the lower gastrointestinal tract [29,30]. Most of the studies conducted to date have shown that Blastocystis colonization is associated with a higher bacterial diversity of gut microbial communities [25][26][27]. However, in contrast, in the present study we found that the presence of Blastocystis ST7 was associated with a lower bacterial diversity.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…A reduction in intestinal microbiota diversity has been observed in a series of digestive diseases, such as IBD and IBS, that are associated with inflammation of the lower gastrointestinal tract [29,30]. Most of the studies conducted to date have shown that Blastocystis colonization is associated with a higher bacterial diversity of gut microbial communities [25][26][27]. However, in contrast, in the present study we found that the presence of Blastocystis ST7 was associated with a lower bacterial diversity.…”
Section: Discussioncontrasting
confidence: 83%
“…Several studies have investigated the associations between Blastocystis colonization and diversity of the gut bacterial microbiota [7,10,[24][25][26][27]. Microbial diversity is considered to be a potential biomarker of a healthy gut, and higher diversity means stability and resilience of the gut ecosystem [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the presence of Blastocystis sp. was associated with enriched Firmicutes and Bacteroidetes, and the genera Prevotella, Faecalibacterium, Flavonifractor, Clostridium, Succinivibrio , and Oscillibacter , whereas Proteobacteria and the genera Escherichia, Bacteroides, Klebsiella , and Pseudomonas were enriched in Blastocystis sp.-negative group ( 105 ).…”
Section: The Correlation Between Blastocystis Sp A...mentioning
confidence: 99%
“…blastocystosis is a unicellular parasitic protozoon, which has been detected globally, with up to 100% prevalence 18 . It inhabits the large intestine of humans and animals and is sometimes present in intestinal microbiomes with eubiosis 19 . Blastocystosis, human infection by blastocystosis , has various outcomes: it can be asymptomatic in infected patients, can produce diarrhea and other gastrointestinal symptoms, or have an opportunistic character and cause infection in immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%